Pemanfaatan Teknologi dalam Peningkatan Kualitas Pendidikan Agama Islam - Hanifah Salsabila, Unik; Albana , Rifaah Salwa; Mailandari, Olvy; Iskandar , Utut Abdillah; Pratiwi, Anggi (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2022)
As time passes, society evolves more and more. The dynamism of the current era facilitates occasional technological advancements. Academics, particularly educators, must find ways to incorporate technology into a variety of educational activities in order to keep up with the rapid pace of technological development. This article aims to provide an overview of the numerous ways in which technology can be used to improve the quality of education in light of recent technological advancements by examining the previously stated notions. Existing technological advancements in education include learning software, E-learning, and other online platforms that assist educational activities. Technological advancements have a significant impact on the learning process in schools. Among the benefits of technology is enhancing students' Islamic education-related perspectives. Educators are deemed qualified based on their ability to instruct; hence, they must be able to utilize technology effectively. This study was conducted utilizing a qualitative approach and literature review methodologies. Examining scientific journals and books about the use of technology to enhance the quality of learning yielded the necessary data. After collecting data, the author analyzes and develops the data into writing. Our research demonstrates that technology plays various crucial roles in education, particularly in Islamic education. Contemporary students are hesitant to pursue Islamic education. Why is this so? Because during the learning process, Islamic education is deemed to be somewhat monotonous. Thus, many students find Islamic education tedious and tedious.